Determination of the Chronological Order of a Laser Printing and Gel Pen Writing Without any Crossing Strokes. Issue 4 (18th February 2020) - Gupta, Vinayak; Saini, Komal
Abstract: Laser printers and writing instruments are being exploited by the forgers to produce fabricated documents. They often produce such documents by appending genuine signature on a blank sheet and later printing on it. Often these fabricated documents do not contain intersection of strokes and may pose a difficulty to forensic document examiners in analyzing cases related to such documents. Keeping in mind the limited research work done on nonintersecting strokes, the present study has been conducted with an aim to determine the sequence of nonintersecting strokes of gel pens and laser printers. Three hundred samples of nonintersecting strokes of gel pen ink and laser printing were prepared. Of these 300, 150 had laser‐printed text below the gel pen strokes and the remaining 150 were prepared with gel pen stokes below the laser‐printed text. The samples have been analyzed using Nikon SMZ 800N stereomicroscope. Three micro‐conformation features, that is, pattern of toner distribution, ink distribution, and fiber distribution have been observed in the samples. The results demonstrate the successful establishment of sequence of nonintersecting strokes in case of gel pen and laser‐printed documents by the determination of micro‐conformation features.